ABANDONMENT, COPYRIGHT AND ORPHANED WORKS: WHAT DOES IT MEAN TO TAKE THE PROPRIETARY NATURE OF INTELLECTUAL PROPERTY RIGHTS SERIOUSLY? - Hudson, E; Burrell, R (2011)
For many years there was doubt as to whether personal property could be abandoned. In more recent times, however, the existence of a doctrine of abandonment has been solidifying in relation to chattels. In this article the authors suggest that copyright works can also be abandoned. This conclusion has significant implications for cultural institutions and other users struggling to deal with so-called 'orphaned works'. More generally, the authors suggest that recognising that abandonment of copyright is possible has repercussions for how we think about intellectual property rights and, in particular, should cause us to look more closely at other doctrines within the law of personal property that might limit intellectual property's reach.